2018
DOI: 10.1002/jmri.26580
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative histopathologic assessment of perfusion MRI as a marker of glioblastoma cell infiltration in and beyond the peritumoral edema region

Abstract: Background Conventional MRI fails to detect regions of glioblastoma cell infiltration beyond the contrast‐enhanced T1 solid tumor region, with infiltrating tumor cells often migrating along host blood vessels. Purpose To quantitatively and qualitatively analyze the correlation between perfusion MRI signal and tumor cell density in order to assess whether local perfusion perturbation could provide a useful biomarker of glioblastoma cell infiltration. Study Type Animal model. Subjects Mice bearing orthotopic gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…The current study has some limitations: (i) a histopathological confirmation of tumor infiltration beyond the enhancing part of the tumor and beyond the areas of prolonged T2 was not performed, as the resection of brain tissue which was not suspicious in conventional MRI would not be justifiable ethically. However, recent preclinical studies show that glioma cell infiltration reaches beyond the area of signal hyperintensity in T2w images; (ii) to reduce the scanning time, T2 mapping was restricted to 25 slices covering a slab of 5 cm. Therefore, in some patients, the edema region was not completely covered, which may have changed quantitative values for the edema region slightly; and (iii) it should also be noted that CA accumulation remains only an indirect sign of potential glioma cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study has some limitations: (i) a histopathological confirmation of tumor infiltration beyond the enhancing part of the tumor and beyond the areas of prolonged T2 was not performed, as the resection of brain tissue which was not suspicious in conventional MRI would not be justifiable ethically. However, recent preclinical studies show that glioma cell infiltration reaches beyond the area of signal hyperintensity in T2w images; (ii) to reduce the scanning time, T2 mapping was restricted to 25 slices covering a slab of 5 cm. Therefore, in some patients, the edema region was not completely covered, which may have changed quantitative values for the edema region slightly; and (iii) it should also be noted that CA accumulation remains only an indirect sign of potential glioma cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Values between the VOIs differ significantly at the P < 0.01 level when indicated with * above the arrows. Only the values between edema and 5 mm zone for the relative qT1-difference and the absolute T1w difference were not significant (indicated with "ns" above the arrows) T2w images 35,36 ; (ii) to reduce the scanning time, T2 mapping was restricted to 25 slices covering a slab of 5 cm. Therefore, in some patients, the edema region was not completely covered, which may have changed quantitative values for the edema region slightly; and (iii) it should also be noted that CA accumulation remains only an indirect sign of potential glioma cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-infiltration is often ill-defined in glioblastoma using contrast-enhanced T1W MRI. Perfusion imaging conducted at UHF illustrated that regions of low tumour infiltration could be probed even in and beyond the oedematous T2 hyperintensity region surrounding macroscopic tumour [50]. UHF anatomical and DW MRI have also been reported as efficient for partial nephrectomy in small renal masses indicating a potential use in perioperative assessment with a maximal sparing or renal parenchyma without compromising oncological outcomes, similarly to sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, in most of the cases the CRM status was easily established by in-vivo MRI, and routine use of smr might be unrealistic. However, small-sized MRI scanners have been developed already for small animals [27], and if some kind of MRI image navigation system for making sections were available in routine work, the pathological diagnostic ability would be improved. In this study, we have shown that the pCRM can be estimated by smrCRM more accurrately, which can reduce the risk of misreading the pCRM status.…”
Section: Discussionmentioning
confidence: 99%